A New Method for Standardizing Inland Fish Community Surveys: Characterizing Habitat Associated with Small-Bodied Fish Species, Abundance, and Size Distributions in a Highly Modified Estuary - Merz, Joseph E.; Camp, Meghan J.; Simonis, Juniper L.; Thorpe, Whitney (Frontiers in Environmental Science, 2021)
Monitoring fish assemblages in estuary environments is often difficult to standardize due to habitat complexity and gear-specific selectivity. This is further compounded by conventional sampling methods which require fish handling that might cause stress or mortality. To ameliorate these issues, we developed the Single-Platform Aquatic Species and Habitat Sampling System (Platform), an integrated and mobile concentrator net and live box prototype, coupled with a range of physical monitoring equipment. We investigated the utility of the Platform over a short time period (two months) in a relatively small and complex embayment within the highly modified San Francisco Estuary, California. We were able to identify clear physical distinctions among estuary/delta habitat types and detect habitat segregation by ecological groups of sampled fishes with the Platform. The Platform also detected discernable ontogenetic shifts (i.e., size differences) within estuary habitats of commonly observed fish species. These initial results suggest the Platform can potentially fill a methodological gap in non-invasive surveying of small-bodied fish across a range of estuarine habitats, warranting further investigation of potential applications, including passive video monitoring.